Smallholder Farmers Satisfaction with Agricultural Information for Enhancing Climate Change Adaptation in Mbogwe District, Tanzania - Sawe, Jackson Raymond (University of Dar es Salaam Library Journal, 2025)
This article examines the satisfaction of smallholder farmers with the agricultural information used for climate change adaptation in Mbogwe District, Tanzania. It examines the types and availability of information, farmers’ satisfaction levels, and the reasons for dissatisfaction. Using a mixed-methods approach that combines both quantitative and qualitative data, the study involved 300 smallholder farmers. Findings indicate that 59 per cent of farmers were satisfied with the information, citing benefits such as guidance on planting dates, improved conservation practices, enhanced knowledge, and increased awareness of crop production. In contrast, 41 per cent were dissatisfied due to a lack of, delays in, or non-specific information. The research highlights that access to relevant agricultural information boosts farmers’ ability to adapt to climate change. Enhancing dissemination methods can improve climate resilience and support sustainable farming practices. Stakeholders should focus on providing timely, context-specific, and accessible information that is relevant to their audience. However, since the study is limited to Mbogwe District, its findings may not be fully applicable elsewhere. Additionally, it did not thoroughly examine external factors, such as market conditions and government policies. Future research should investigate these broader influences to develop more comprehensive adaptation strategies. Keywords: Smallholder farmers, Satisfaction, Agricultural information, Climate change, Adaptation https://dx.doi.org/10.4314/udslj.v20i1.3